The usefulness of the teacher from taking a class, and the productivity of the process of education - Ejsmont, Wiktor (Użyteczność nauczyciela z prowadzenia lekcji a wydajność procesu edukacji, 2010)
The author of the article is focusing on the explanation how productivities of the process of the education are being exchanged at the maximization of the so-called model of the profit of the education. This model was introduced and described by Bosworth and Caliendo (2007). The fact that it is taking into consideration the satisfaction of the teacher from lecturing a chosen group pupils is an innovative part of this model. The majority of the article is relying on six theorems presented by Bosworth and Caliendo and on proving two new theorems (one of which is an extension of the results received by the mentioned authors). Received results will be illustrated with proper simulations.
Mathematical Economics, 2010, Nr 6 (13), s. 33-48
Keywords: production functions of the education; preferences of the teacher; optimum size of the class